Antibacterial and Antifungal Property of Actinomycetes Isolates from Soil and Water of Nepal - Lekhak, Binod; Singh, Anjana; Bhatta, Dwij Raj (Journal of Nepal Health Research Council, 2018)
Background: Human pathogens are rapidly acquiring resistance to antibiotics leading to treatment failure. We carried out this study to isolate and screen actinomycetes strains that have potential to kill bacterial and fungal pathogens. Methods: In this descriptive study 288 soil and water samples were processed by standard microbiological techniques at Central Department of Microbiology,Tribhuvan University from 2013 to 2015. Screened actinomycetes were cultivated for bioactive metabolite production and minimum inhibitory concentration (MIC) of metabolites were determined against bacterial pathogens including multidrug resistant bacteria and fungi. Results: One hundred twenty isolates having antimicrobial property were screened. Out of them, four most potent strains, Nocardiopsis prasina, Streptomyces violarus, Streptomyces krainskii and Streptomyces tsusimaensis were identified all having both antibacterial and anti-fungal property.Highest zone of inhibition (ZOI)was given by N. prasina against Candida albicans(41.33 ±1.15mm) and among bacteria, maximum ZOI was against Acinetobacter baumannii(31.33±3.05mm). MIC value of metabolite of N.prasina was 0.125mg/ml for E.coli and C. albicans. It was 2.5 mg/ml each for methicillin resistant Staphylococcus aureus (MRSA), A. baumannii and Salmonella Typhi and 0.625 mg/ml for Bacillus Subtilis. Conclusions: Bioactive metabolite producing actinomycetes were recovered from soil and tested against human pathogenic bacteria and fungiand found to have antibacterial and antifungal property. Keywords: Actinomycetes; bioactive metabolite; MIC; zone of inhibition.